Analysis of factors influencing customer satisfaction dkriuk fried chicken serua using PLS-SEM - Mahardika, Dikki; Surjasa, Dadang; Safitri, Dian Mardi (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
One of the food menus that can be eaten at every meal is fried chicken. As the fried chicken franchise culinary business grows in the Jabodetabek area, trade competition to win the hearts of consumers is getting higher. Dkriuk Fried Chicken (DFC) Serua is a fried chicken culinary business. Understanding consumer needs is very important because a culinary business needs regular customers to survive. The decrease in the chicken frying business and the existence of similar business competition around the location need to be researched. This study aimed to determine the effect of price, product, service and relationship management with customers on customer satisfaction. The analysis was carried out partially on each variable. This study conducted a correlation test between variables using the PLS-SEM approach using SmartPLS version 3. Based on the data obtained by distributing questionnaires to 76 DFC Serua consumers who came directly, the analysis of the relationship between variables was obtained. Product variables have a significant influence on customer satisfaction. Price has a significant influence on customer satisfaction. Service has no significant effect on customer satisfaction. Relationship management with customers has no significant effect on customer satisfaction.